A High Performance Terahertz Waveguide Detector Based on a Low-Barrier Diode - 任田昊 张勇 延波 徐锐敏 杨成樾 周静涛 金智 (Chinese physics letters, 2016)
A Schottky barrier diode with low-barrier is presented, based on which a terahertz waveguide detector working at 500-600 GHz is designed and fabricated. By using the InGaAs/InP material system, the feature of the low barrier is obtained which greatly improves the performance of the detector. The measured typical voltage responsivity is about 900 V/W at 50-560 OHz and is about 400 V/W at 560 600 GHz. The proposed broadband waveguide detector has the characteristics of simple structure, compact size, low cost and high performance, and can be used in a variety of applications such as imaging, moleeuIar spectroscopy and atmospheric remote sensing.